Kosenko Yu. Peculiarities of the non-verbal means of communication in the cross-cultural interaction - Kosenko Yu. (Philological Treatises, 2020)
The article is devoted to the non-verbal means of communication in the cross-cultural interaction. Special attention is focused on the paralinguistic nature of different paradigm of units, especially facial expression, eye- contact, smile, distance factors of the partners, posture, gestures, which substitute words or accompany conversation. Studies have shown these non-verbal elements to be the most culturally – influenced part of behaviour. Attention is being paid to the non-verbal means of communication as harmonious interaction to minimize the possibility of conflict. The study of communicant’s speech behaviour in concrete situations allowed to define peculiarities of the non-verbal means used to convey emotions, intentions, information in different countries.